Proyecto de inversión para el incremento de producción de rosas de exportación en el mercado ruso de la empresa Hispanoroses Cia Ltda ubicada en Tanicuchi, provincia de Cotopaxi-Ecuador - Fiallos Escobar, Fanny Raquel (2015)
This research was conducted in the parish Tanicuchi, Canton Latacunga, Cotopaxi province, whose purpose is to develop an investment project to increase production of export roses in the company HISPANOROSES CIA. LTDA.To the Russian market. The importance of the project prior to implementation investment ensures the success or failure of it. Export demand rose to the Russian market is constant and growing every year, so that the current supply is reduced and production alternatives are becoming necessary, but require the long-term economic viability to invest in the sector. The investment income is a source for the development of the Ecuadorian economy to generate foreign exchange and be the engine of thousands of places of direct and indirect jobs. Therefore the company is required to maintain the status of being excellent competitors in any market in the world, as it constitutes a window to the outside Ecuador and an example for potential investors. The overall objective of this study is to study investment to determine the economic viability of increased production of export roses in the company HISPANOROSES CIA LTDA. To this end the business idea is identified, drawing on the experience of the company has production and market demand. The research methods that were used are descriptive, deductive, inductive, historical and scientific method. Among the techniques used are library research, interview and survey. As a starting point is taken as the result of market research, which after field research a demand for 18,900 tons of roses are determined within the period 2014. Similarly was established that the existing supply is de18122 tons of roses . Within the technical study could determine the installed capacity with which the company that is 10 hectares of the total area. Based on information obtained from geographical maps, identify the location of the company, which is located in Santa Clara Sector Coba, Tanicuchi parish belongs to the canton Latacunga Cotopaxi province, to a length of 78 ° 38' 45 "latitude and 0 ° 46'05". Engineering project has been planned in two aspects: the development of infrastructure and productive development. With regard to administrative parameters the company is a limited liability organization must establish qualified staff will contribute to the objeticos proposed at different hierarchical levels of the company. According to the results of the financial research, investment of the project is $ 243,696.97, funded by the Banco de Pichincha to an interest rate of 9.53% over four years within months. As regards the financial evaluation have resulted in the project is feasible to perform, since the results are favorable, and are as follows: The Net Present Value gives a positive value of $ 224,193.97 which means that the value of the company improved during production stage; The Internal Rate of Return, gives us a result of 22%, which means that is higher than the percentage value that the bank provides the credit; The benefit / cost, gives us a result greater than 1, meaning that for every dollar invested will get 0,75centavos dollar returns; The investment will pay off in five years, two months. Through the analysis in the research and about the results you can set the viability of the project from an administrative and financial technically market, resulting in positive figures that will benefit the project once it is put on going. Finally finds the respective conclusions and recommendations